Approaches to big data analysis of interface pressure measurements from continuous pressure imaging technology. (2018) - Peng, Mingkai; Ocampo, Wrechelle; Southern, Danielle; Baylis, Barry; Hogan, David; Conly, John; Stelfox, Thomas; Kaufman, Jaime; Ghali, William; Ho, Chester
No abstract available